2013
DOI: 10.1128/jvi.02856-12
|View full text |Cite
|
Sign up to set email alerts
|

The Source of the PB1 Gene in Influenza Vaccine Reassortants Selectively Alters the Hemagglutinin Content of the Resulting Seed Virus

Abstract: The yields of egg-grown influenza vaccines are maximized by the production of a seed strain using a reassortment of the seasonal influenza virus isolate with a highly egg-adapted strain. The seed virus is selected based on high yields of viral hemagglutinin (HA) and expression of the surface antigens from the seasonal isolate. The remaining proteins are usually derived from the highgrowth parent. However, a retrospective analysis of vaccine seeds revealed that the seasonal PB1 gene was selected in more than 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
41
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 37 publications
13
41
0
Order By: Relevance
“…Our own retrospective analysis of past vaccine seed strains available at bioCSL, Ltd. (8), is in agreement with other similar analyses that indicate that most of the non-HA and NA genes are derived from the high-growth parent. However, the seasonal PB1 gene dominates in progeny viruses in about 50 to 60% of reassortment events.…”
supporting
confidence: 73%
“…Our own retrospective analysis of past vaccine seed strains available at bioCSL, Ltd. (8), is in agreement with other similar analyses that indicate that most of the non-HA and NA genes are derived from the high-growth parent. However, the seasonal PB1 gene dominates in progeny viruses in about 50 to 60% of reassortment events.…”
supporting
confidence: 73%
“…ratios (Tables 1 and 2). In another study, it was shown that the PB1 segment derived from the seasonal H3N2 virus A/Udorn/307/72 (Udorn) helped to improve the PR8-based 5+3 IVS carrying HA/NA/ PB1 Undorn by a fourfold increase of the HA content per virion, even though this IVS was replicating less efficiently than the corresponding 6+2 IVS (Cobbin et al, 2013). Yet our results, which are consistent with those of a previous study by Harvey et al (2011), demonstrate that the HA yield of our IVSs rather depends on virus growth rate than on HA content per viral particle.…”
Section: Discussionmentioning
confidence: 99%
“…Given that virus neutralization requires antibodies that recognize specific epitopes on the HA protein, a high HA content per virion allows to increase the overall amount of produced vaccines (Cobbin et al, 2013). We therefore sought to rule out the possibility that enhanced replication of 5+2+1 IVSs resulted in virus particles with reduced HA content.…”
Section: Pb1 Gi Enhances the Replication Of Pr8-derived Ivss With DIVmentioning
confidence: 99%
See 1 more Smart Citation
“…PB1 from a seasonal strain or with targeted mutations has been shown to improve growth or HA yield of H3 reassortants (Cobbin et al, 2013;Plant et al, 2012); however, mixed results have been observed for H5 reassortants (Abt et al, 2011;Rudneva et al, 2007;Wanitchang et al, 2010). All three polymerase segments reassort together more frequently in experimental settings than natural reassortment, suggesting gene constellation effects (Macken et al, 2006;Varich et al, 2008;Wille et al, 2013).…”
mentioning
confidence: 99%